Enuresis In children- A study From Western Maharashtra - LAWAND, SUNIL; PRASANNA, M. V. N. L. (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The word enuresis is gotten from a Greek word (enourein) that signifies "to void pee." It can happen either during the day or around evening time (however some limit the term to bedwetting that happens around evening time). Enuresis can be divided into primary and secondary forms. Aim of current study was to find out the prevalence, underlying risk factors and management of nocturnal enuresis in age groups 4 to 15 years in the patients attending OPD in KIMS,Karad.Methods: The study was done during the year 2018-19 among 100 school going age children attending OPD with complaint of enuresis, with the cooperation of the parents of the children. Results:Nocturnal enuresis was more common in males than in females, 68/100 in males and 32/100 in female children. Conclusions:Our revelations recommend that evening time enuresis is a run of the mill issue among more youthful understudies especially with low compensation, lower age, family parentage of enuresis and history of urinary tract sickness. Enuresis is a pediatric general clinical issue and tries at all levels should be made, for instance, preventive, etiological and restorative. The extent of folks to females in this examination was 2.12 that is comparable to other data of a comparative report.